Angiospermic Plant Diversity Of Sandwip Island, Chittagong, Bangladesh - Sajib, Noor Hassan; Uddin, SB; Pasha, Mostafa Kamal (Journal of the Asiatic Society of Bangladesh, Science, 2015)
A survey of angiospermic plant diversity of Sandwip Island, Bangladesh has conducted from July 2008 to June 2012. This study recorded 457 species under 317 genera of 104 families including cultivated and planted. On the basis of habit distribution herbs are represented by 232, shrubs 71, trees 113 and climbers by 41 species. For each species scientific name, local name, family and habit character have been presented. Plant species of the area are at risk because of drought, salinity, anthropogenic activities and continuous bank erosion in the sea and shifting of land. Asiat. Soc. Bangladesh, Sci. 41(2): 133-153, December 2015